The Effect of Organizational Justice on Turnover Intention Mediated by Organizational Commitment - Giffary Ryan Fauza; Nazaruddin Malik; Aniek Rumijati (Universitas Muhammadiyah Malang, 2022)
The purpose of this study was to determine the effect of organizational justice on turnover intention mediated by organizational commitment in PT Kaltim Post Samarinda. This type of research uses explanatory research with a quantitative approach totaling 54 respondents. The source of data in this study was obtained from the distribution of questionnaires (primary data). The data analysis technique used path analysis. The results show that organizational justice has a positive and significant effect on organizational commitment. Meanwhile, organizational justice has a negative and significant effect on turnover intention. Organizational commitment has a negative and significant effect on the intention to leave the company and organizational commitment is proven as a variable that mediates the relationship between organizational justice and turnover intention